Effect of Storage Temperature on the Phenotype of Cultured Epidermal Cells Stored in Xenobiotic-Free Medium. (2nd June 2016) - Jackson, Catherine; Eidet, Jon R.; Reppe, Sjur; Aass, Hans Christian D.; Tønseth, Kim A.; Roald, Borghild; Lyberg, Torstein; Utheim, Tor P.
Abstract: Purpose : Cultured epidermal cell sheets (CECS) are used in the treatment of large area burns to the body and have potential to treat limbal stem cell deficiency (LSCD) as shown in animal studies. Despite widespread use, storage options for CECS are limited. Short-term storage allows flexibility in scheduling surgery, quality control and improved transportation to clinics worldwide. Recent evidence points to the phenotype of cultured epithelial cells as a critical predictor of post-operative success following transplantation of CECS in burns and in transplantation of cultured epithelial cells in patients with LSCD. This study, therefore assessed the effect of a range of temperatures, spanning 4–37 °C, on the phenotype of CECS stored over a 2-week period in a xenobiotic-free system. Materials and Methods : Progenitor cell (p63, ΔNp63α and ABCG2) and differentiation (C/EBPδ and CK10) associated marker expression was assessed using immunocytochemistry. Immunohistochemistry staining of normal skin for the markers p63, ABCG2 and C/EBPδ was also carried out. Assessment of progenitor cell side population (SP) was performed using JC1 dye by flow cytometry. Results : P63 expression remained relatively constant throughout the temperature range but was significantly lower compared to control between 20 and 28 °C ( p < 0.05). High C/EBPδ together with low p63 suggested more differentiation beginning at 20 °C and above. Lower CK10 and C/EBPδ expression most similar to control was seen at 12 °C. The percentage of ABCG2 positive cells was most similar to control between 8 and 24 °C. Between 4 and 24 °C, the SP fluctuated, but was not significantly different compared to control. Results were supported by staining patterns indicating differentiation status associated with markers in normal skin sections. Conclusions : Lower storage temperatures, and in particular 12 °C, merit further investigation as optimal storage temperature for maintenance of undifferentiated phenotype in CECS.